Carbon Accounting in Harvested Wood Products: Assessment Using Material Flow Analysis Resulting in Larger Pools Compared to the IPCC Default Method - Gediminas Jasinevičius; Marcus Lindner; Emil Cienciala; Markku Tykkyläinen (Journal of Industrial Ecology, 2018)
Summary Increasing the amount of carbon stored in harvested wood products (HWPs) is an internationally recognized measure to mitigate climate change. Several approaches and tiers of methods may be used to analyze the contribution of HWP in terms of greenhouse gas emissions and removals at a regional and national level. The Intergovernmental Panel on Climate Change (IPCC) provides guidelines on three tiers of methods for estimating annual carbon stock changes in the carbon pool of HWPs. These tiers mostly differ by the availability of input data and the level of HWP aggregation. In this case study for the Czech Republic, we have applied the production approach and alternative tiers of accounting methods, which are described in the IPCC guidelines, including the default method (tier 2) and the most advanced method (tier 3). We used country‐specific data and material flow analysis to trace the carbon flow over the entire forest‐based sector, including only the domestic harvest and the primary and secondary wood products manufactured within the country. The results of this study show that the carbon stored in the HWP pool could be underestimated if simpler methods and default values nonspecific to the country are applied. At the national level, applying the tier 3 method resulted in a 15.8% higher annual carbon inflow in the pool of HWPs compared to the tier 2 IPCC default method. This means that the advanced method reveals an apparently higher carbon sink in HWPs. A documented increase of carbon storage might bring additional credits to reporting countries, and, more important, it could promote the use of long‐life HWPs to mitigate climate change.